2011
DOI: 10.1177/0884533611426148
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition Improves Outcomes of Open Abdomen in Gastrointestinal Fistula Patients Complicated With Severe Sepsis

Abstract: Nutrition therapy plays an important role in the management of gastrointestinal fistula with severe sepsis. Early EN could be successfully delivered for that population, with improved mortality risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The most serious complication associated with open abdomen therapy is gastrointestinal fistula [51]. Other complications, such as wound infection, intra-abdominal abscess, and recurrent hernia, are commonly reported.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious complication associated with open abdomen therapy is gastrointestinal fistula [51]. Other complications, such as wound infection, intra-abdominal abscess, and recurrent hernia, are commonly reported.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-institutional study demonstrated that EN after an open abdomen was associated with increased fascial closure rates, reduced complications rates, and improved mortality [53]. Besides, early EN could now be delivered successfully via various approaches in patients with IAI, with reduced fistula formation and improved mortality rates [54, 55]. This early initiation of enteral feeding was reported to be an independent predictor of successful fascial closure in OA patients complicated with intestinal fistula [45].…”
Section: The Open Abdomen In Treatment Of Intra-abdominal Infectionmentioning
confidence: 99%
“…Individualizing the nutritional management plan in terms of caloric and protein requirements and feeding route has been recommended in several studies 6,11,24…”
Section: Discussionmentioning
confidence: 99%